Case Report: Novel likely pathogenic MEN1 mosaic mutation in the family with MEN-1 syndrome - Salimkhanov, Rustam; Utkina, Marina; Bagirova, Hanum; Eremkina, Anna; Prosandeeva, Ekaterina; Popov, Sergey; Zakharova, Victoria; Petrov, Vasiliy; Novoselov, Alexey; Bondarenko, Ekaterina; Pastukhova, Daria; Rozhinskaya, Lyudmila; et al. (Frontiers in Endocrinology, 2025)
Multiple endocrine neoplasia type 1 (MEN-1; OMIM 131100) is a rare, autosomal dominant syndrome caused by heterozygous inactivating mutations in the MEN1 tumor suppressor gene (11q13; OMIM 613733). MEN-1 is characterized by polyglandular pathology, which typically involves the parathyroid glands (90%), pancreas (30-80%) and anterior pituitary (15-50%). To date, over 1,600 pathogenic MEN1 variants have been documented, including nonsense, frameshift, and splice-site mutations, as well as rare large deletions. While germline mutation detection rates reach 70-90% in clinically diagnosed probands, approximately 10-30% of phenotypically confirmed MEN-1 families test negative by conventional sequencing, suggesting possible regulatory region defects, deep intronic mutations, or mosaic variants. In cases where MEN1 germline testing is negative despite a clinical MEN-1 phenotype, somatic mosaicism should be considered. We investigated a familial cohort presenting with primary hyperparathyroidism, multifocal pancreatic and pituitary neuroendocrine neoplasms – a triad strongly suggestive of MEN-1. Using a multi-tissue sequencing approach, we analyzed DNA extracted from peripheral blood leukocytes and parathyroid adenomas tissue via both Sanger sequencing and next-generation sequencing (NGS) with high coverage. While conventional Sanger analysis failed to detect a mutation, targeted NGS revealed a novel, likely pathogenic MEN1 variant present at low allele frequency (5-15%), consistent with postzygotic mosaicism. The variant was classified as pathogenic per ACMG/AMP guidelines and correlated with disease manifestations in affected tissues. These findings demonstrate that high-coverage NGS of multiple tissues is critical for identifying low-level mosaic MEN1 mutations missed by standard testing. Alternative screening methods are required for patients with strong clinical indications of MEN-1 and/or a family history, but negative germline test results, one such method is NGS with high coverage.